Dry liquid metals stabilized by silica particles: Synthesis and application in photothermoelectric power generation - Manyuan, Nichayanan; Otsuki, Tomoko; Tsumura, Yusuke; Fujii, Syuji; Kawasaki, Hideya (Journal of colloid and interface science, 2023)
[Display omitted] Gallium-based room-temperature liquid metals (LMs) have unique physicochemical properties; however, their high surface tension, low flowability, and high corrosiveness to other materials limit their advanced processing (including precise shaping) and application. Consequently, LM-rich free-flowing powders, named “dry LMs” that offer the inherent advantages of dry powders, should play a critical role in expanding the application scope of LMs. A general method of preparing silica-nanoparticle-stabilized LMs in the form of LM-rich powders (>95 wt% LM) is developed. Dry LMs can be simply prepared by mixing LMs with silica nanoparticles in a planetary centrifugal mixer in the absence of solvents. As a sustainable dry-process route alternative to wet-process routes, this ecofriendly and simple method of dry LM fabrication has several advantages, e.g., high throughput, scalability, and low toxicity owing to the lack of organic dispersion agents and milling media. Moreover, the unique photothermal properties of dry LMs are used for photothermal electric power generation. Thus, dry LMs not only pave the way for the use of LMs in powder form but also provide a new opportunity for expanding their application scope in energy conversion systems.